A Framework for Dynamic Context-Centric Commander Decision Support. (September 2016) - Santos, Eugene; Nguyen, Hien; Russell, Jacob; Day, Joshua; Pegleow, Scott; Greenstreet, Alexis
This paper addresses the fundamental research question: "How can we determine the sequential decision- making process inside a decision maker's mind?" We construct a dynamic Markov Decision Process using a Double Transition Model (DTM). The DTM is a cognitive model decomposing the decision-making process into episodic tasks that are extracted from a stream of incoming information. In a DTM, each state reflects a stage en route to a decision, and each action reflects a possible move from collecting data to hypothesizing and inferencing. The reward reflects how close a stage is to the final decision. We demonstrate this process through a proof-of-concept DTM using a hypothetical scenario for Typhoon Haiyan in the Philippines (2013). The DTM constructed from this scenario enables a Commander to reason about damaged areas, death tolls, and assistance methods while allowing his actions to be captured and used to explain why and how each decision is made.